Unlawful activities (prevention) act, 1967 (act no. 37 of 1967) - Shree ram law house; Bare Act (Chandigarh Shree Ram Law House, 2024)
Unlawful activities (prevention) act, 1967 (act no. 37 of 1967) as amended by the unlawful activities (prevention) amendment act, 2019 (28 of 2019).
Keywords: Unlawful Activities Act